Baroreceptor unloading in postural tachycardia syndrome augments peripheral chemoreceptor sensitivity and decreases central chemoreceptor sensitivity - Taneja, Indu; Medow, Marvin S.; Clarke, Debbie A.; Ocon, Anthony J.; Stewart, Julian M. (American journal of physiology. Heart and circulatory physiology, 2011)
While orthostatic tachycardia is the hallmark of postural tachycardia syndrome (POTS), orthostasis also initiates increased minute ventilation (V̇e) and decreased end-tidal CO 2 in many patients. We hypothesized that chemoreflex sensitivity would be increased in patients with POTS. We therefore measured chemoreceptor sensitivity in 20 POTS (16 women and 4 men) and 14 healthy controls (10 women and 4 men), 16–35 yr old by exposing them to eucapneic hyperoxia (30% O 2 ), eucapneic hypoxia (10% O 2 ), and hypercapnic hyperoxia (30% O 2 + 5% CO 2 ) while supine and during 70° head-upright tilt. Heart rate, mean arterial pressure, O 2 saturation, end-tidal CO 2 , and V̇e were measured. Peripheral chemoreflex sensitivity was calculated as the difference in V̇e during hypoxia compared with room air divided by the change in O 2 saturation. Central chemoreflex sensitivity was determined by the difference in V̇e during hypercapnia divided by the change in CO 2 . POTS subjects had an increased peripheral chemoreflex sensitivity (in l·min −1 ·%oxygen −1 ) in response to hypoxia (0.42 ± 0.38 vs. 0.19 ± 0.17) but a decreased central chemoreflex sensitivity (l·min −1 ·Torr −1 ) CO 2 response (0.49 ± 0.38 vs. 1.04 ± 0.18) compared with controls. CO 2 sensitivity was also reduced in POTS subjects when supine. POTS patients are markedly sensitized to hypoxia when upright but desensitized to CO 2 while upright or supine. The interactions between orthostatic baroreflex unloading and altered chemoreflex sensitivities may explain the hyperventilation in POTS patients.